Divergent structural and functional brain alterations in HIV-infected patients: a multimodal meta-analysis - Li, Zhong; Jin, Xingxing; Zhang, Meng; Wang, Hongxia; Liu, Wangyi; Wang, Beiran; Wu, Baolin; Li, Xuekun (Frontiers in Neurology, 2025)
Neuroimaging studies have identified brain structural and functional alterations in HIV-infected patients; however, the results are inconsistent. This study aimed to characterize the effects of HIV infection on regional gray matter volume (GMV) and resting-state brain activity, and to further investigate the relations between abnormalities in these two modalities. We conducted voxel-wise meta-analysis of voxel-based morphometry (VBM) and functional studies, respectively, to identify regional GMV and brain activity alterations in HIV-infected patients. Multimodal analysis was performed to examine the overlap of regional GMV and brain activity alterations. Meta-regression analysis was conducted to evaluate the potential effects of clinical variables. Eleven whole-brain VBM studies and eight resting-state functional studies were included. HIV-infected patients showed structural abnormalities alone in the bilateral medial prefrontal cortex/anterior cingulate cortex, bilateral calcarine cortex and left amygdala, and had functional abnormalities alone in the left middle frontal gyrus, left parahippocampal gyrus, left superior temporal gyrus and visual cortices. No conjoint brain structural and functional abnormalities were identified. This study characterized dissociated brain structural and functional alterations in HIV-infected patients from a perspective of multimodal meta-analysis, which may provide new insights into the neurobiology of HIV-associated neurocognitive impairment.